Non-invasive brain stimulation for speech in Parkinson's disease: A randomized controlled trial - Brabenec, Lubos; Klobusiakova, Patricia; Simko, Patrik; Kostalova, Milena; Mekyska, Jiri; Rektorova, Irena (Brain stimulation, 2021)
BACKGROUND: Hypokinetic dysarthria is a common but difficult-to-treat symptom of Parkinson's disease (PD). OBJECTIVES: We evaluated the long-term effects of multiple-session repetitive transcranial magnetic stimulation on hypokinetic dysarthria in PD. Neural mechanisms of stimulation were assessed by functional MRI. METHODS: A randomized parallel-group sham stimulation-controlled design was used. Patients were randomly assigned to ten sessions (2 weeks) of real (1 Hz) or sham stimulation over the right superior temporal gyrus. Stimulation effects were evaluated at weeks 2, 6, and 10 after the baseline assessment. Articulation, prosody, and speech intelligibility were quantified by speech therapist using a validated tool (Phonetics score of the Dysarthric Profile). Activations of the speech network regions and intrinsic connectivity were assessed using 3T MRI. Linear mixed models and post-hoc tests were utilized for data analyses. RESULTS: Altogether 33 PD patients completed the study (20 in the real stimulation group and 13 in the sham stimulation group). Linear mixed models revealed significant effects of time (F(3, 88.1) = 22.7, p < 0.001) and time-by-group interactions: F(3, 88.0) = 2.8, p = 0.040) for the Phonetics score. Real as compared to sham stimulation led to activation increases in the orofacial sensorimotor cortex and caudate nucleus and to increased intrinsic connectivity of these regions with the stimulated area. CONCLUSIONS: This is the first study to show the long-term treatment effects of non-invasive brain stimulation for hypokinetic dysarthria in PD. Neural mechanisms of the changes are discussed.
Keywords: dysartrie; spánkový lalok; Parkinsonova nemoc; Speech Intelligibility; lidé; Dysarthria; Temporal Lobe; Parkinson Disease; srozumitelnost řeči; Humans; transkraniální magnetická stimulace; Transcranial Magnetic Stimulation